The concept nosographic Tropical Medicine - Arce, Julián (1918)
The creation of the department of tropical diseases, I have the honor of running temporarily, has come to meet the urgent need was, to extend, to the extent possible the study of these morbosis, which so closely concern us, relieving the once the heavy work of the course on medical nosography, whose divisions successive imposed by} os advances of modern science, ensuring the effectiveness of teaching and facilitate learning of medicine.